2017
DOI: 10.17750/kmj2017-709
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life of patients operated for chronic pancreatitis

Abstract: Рязанский государственный медицинский университет, г. Рязань, Россия Поступила 03.05.2017; принята в печать 23.06.2017. Р е ф е р а т DOI: 10.17750/KMJ2017-709 Цель. Сравнительный анализ отдалённых результатов хирургического лечения больных хроническим пан-креатитом.Методы. В исследование были включены больные с осложнёнными клиническими формами хронического панкреатита, к которым относятся протоковая панкреатическая гипертензия, конкременты главного панкреа-тического протока, выраженная фиброзная перестройк… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…There were however 9 patients, 7 with slight, and two with moderate disturbances, all within the conservatively treated group. Although this difference was not statistically significant in our 50-patients study, previous studies reported significant improvements within this component [28][29][30][31][32] .…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…There were however 9 patients, 7 with slight, and two with moderate disturbances, all within the conservatively treated group. Although this difference was not statistically significant in our 50-patients study, previous studies reported significant improvements within this component [28][29][30][31][32] .…”
Section: Resultscontrasting
confidence: 89%
“…and pancreatitis specific inventories, and some are demanding to complete 26,33 . Recently, major studies implemented SF12, which was later revised to version 2, and SF8 is also developed [27][28][29][30][31][32][33][34][35] . Patients with CP are usually not in the mood to complete questionnaires, especially when without symptoms, therefore, we aimed to evaluate our outcomes with the use of EQ-5D-5L, as a simplest, but sufficient tool for the QoL assessment 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation